Bolt-free post-tensioned connection for steel-framed modular buildings and design for optimal preloading - Lee, Keunwoo; Rasmussen, Kim J.R.; Cho, Bong Ho (Journal of Constructional Steel Research, 2024)
This paper introduces a novel bolt-free preloaded column-to-column connection, termed the ‘AJ connection’, for steel-framed modular buildings. The AJ connection is classified as a post-tensioned inter-module connection, and modules are connected vertically by preload, using specially designed couplers and high-tensile steel rod bolts (SRB) within the columns. The AJ connection enables easy assembly and disassembly processes of modular buildings by inducing preload on top of the modules using a torque or impact wrench, thus improving construction speed and reusability. The paper also establishes a design method, not previously attempted in the literature, to determine the minimum necessary preload for the connection. The primary aim of this method is to design against potential failures by gap-opening and slip between modules, commonly associated with existing post-tensioned inter-module connections. The effectiveness of the suggested method is verified through numerical simulations using FE joint models that have been calibrated against monotonic loading test results. Furthermore, the study investigates the adverse effects of gap-opening and slip at the connection on the performance of the beam-to-column joint and the SRBs within the columns. The findings indicate that (i) minimising the difference between the flexural stiffness of the floor and ceiling beams reduces the impact of gap-opening, and (ii) the rotation of the coupler caused by plate bearing due to slip prior to gap-opening affects the induced preload in the SRBs and leads to premature gap-opening at the connection.
Keywords: Gap opening; Inter-module; Inter-module connection; Modular buildings; Modular steel building; Modulars; Post tensioned; Post-tensioned connection; Pre loads; Steel buildings; Design; Inter-module connection; Modular steel building; Post-tensioned connection; Prefabricated construction